Toksisitas Ekstrak Kasar Bunga dan Daun Ketepeng Cina (Senna alata L. Roxb.) terhadap Larva Udang Artemia salina Leach - Soetjipto, Hartati; Kristijanto, A. Ign.; Asmorowati, Rica Susy (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
Extract of Candlebush (Senna alata L. Roxb) flowers and leaves show toxicity effect on Artemia salina Leach. The crude extract was obtained by maceration method using methanol 80% and followed by partition into hexane, chloroform and ethylacetate. Data was analized using Randomized Completely Block Design (RCBD) Sub Sampling, that consisted of six treatments, five replications and three sub samples. To compare the differences between the mortality rater of A. salina, the Honestly Significant Differences (HSD) at 5% level of significance was used. Furthermore, to determine the LC50, the probit analysis was used. The results of this study show that the most effective toxin from all fractions of S. alata was the hexane fraction of the leaves extract. The LC50 of S. alata crude extract of leaves was 187,72 ppm (hexane fraction) and 290,34 ppm (EtOAc fraction). The crude extract of S. alata flowers toward A. salina were 210,77 ppm (hexane fraction) and 354,49 ppm (EtOAc fraction). In general, this study showed that all fractions which were tested had the toxic activity on A. salina.